Dynamics and correlations of chlorophyll and phytol content with silage bacterial of different growth heights Pennisetum sinese - Li, Mao; Lv, Renlong; Zhou, Hanlin; Zi, Xuejuan (Frontiers in Plant Science, 2022)
The dynamics and correlations of chlorophyll and phytol content with silage bacterial of different growth heights Pennisetum sinese were investigated. The results demonstrated that the chlorophyll and phytol content of P. sinese before and after ensiled decreased with the increase of growth height. Ensiling significantly reduced pigment content, but had no significant effect on phytol. In addition, P. sinese pigment yield before and after ensiled increased with growth heights increasing, and the yield at 150 or 180cm was obviously higher. Moreover, the silage quality and microbial diversity of P. sinese were vary by growth heights, and some specific undesirable microorganisms were negatively correlated with pigment and phytol content. Therefore, comprehensive consideration of pigment, phytol yield and silage quality, the optimum harvest growth height of P. sinese was 150 cm. Furthermore, precise reduction of particular undesirable microorganisms maybe help to preserve pigments and phytol.